Analyzing the Healthcare Performances of EU Countries via Decision Method - Gökgöz, Fazil; Yalçin, Engin (CRC Press, 2025)
Health systems are one of the most significant structures of any country. Health systems investigated by a multi-criteria decision-making framework determine the social and economic well-being of the nation. EU4Health will contribute to such longer-term goals with its €5.8 billion earmarked for 2021-2027, hence improving health outcomes through frameworks for inclusive and efficient health systems for all EU members. Performance-related issues should be evaluated in accordance with healthcare systems’ particular characteristics. The study employs the entropy technique to ascertain the weights for performance indicators in healthcare and employs PROMETHEE and DOBI techniques in assessing the performance of the EU healthcare system. The data is retrieved from the Eurostat database. Our performance criteria include healthcare expenditure, hospital bed complement, health personnel, and life expectancy at birth. As per the analysis results, Germany ranks first in both years analyzed. Besides, France displays the most influential advancement in 2022 in comparison to the previous year analyzed. Results show the disparities in healthcare performance in the EU countries by highlighting enhancement prospects. The integration of Multi-Criteria Decision-Making methods permits a more structured approach to assessing healthcare performance. The study aims to present detailed insight into the healthcare system of the EU for both practitioners and stakeholders. © 2026 selection and editorial matter, David S-K. Ting and Jacqueline A. Stagner individual chapters, the contributors.
Keywords: Electronic health record; Health care; Personnel; Decision method; EU countries; Health outcomes; Health systems; Healthcare systems; Long-term goals; Multi-criteria decision making frameworks; Performance; Performance indicators; Well being; Decision making